Pengaruh Kepemimpinan dan Kompensasi Terhadap Kinerja Karyawan pada Departemen Solid PT Sanbe Farma Kab. Bandung Barat - Andri AS Rosadi; Dinda Putri Apriliani; Yuda Kusuma Sumadi (Yayasan Literasi Sains Indonesia, 2023)
This research was conducted on employees of PT Sanbe Farma. The purpose of this study was to determine how much contribution the influence of Leadership and Compensation on Employee Performance at PT Sanbe Farma. The methods used in this research are descriptive methods and associative methods. The unit of analysis in this study is an individual, namely PT Sanbe Farma employees. The sample in this study were 84 respondents. The analysis methods used are path analysis, multiple linear analysis, and validity and reliability tests of research instruments. Based on the results of the study it can be concluded that the magnitude of the influence of Leadership on performance at PT Sanbe Farma is 15.1%, the magnitude of Compensation on Performance is 38.5%, the magnitude of Leadership and Compensation on Performance at PT Sanbe Farma is 53.9% so that it can be said that the variables of Leadership and Compensation on (Employee Performance) have a significant effect both partially and simultaneously on employee performance. The implication of this research is to be able to provide a leadership and compensation that has a good effect on PT Sanbe Farma employees in the future.